Alterations in soil phosphorus forms after successive extractions with Mehlich-1, Mehlich-3 and anion exchange resin methods Modificações nas formas de fósforo do solo após extrações sucessivas com Mehlich-1, Mehlich-3 e resina trocadora de ânions - Gatiboni L.C.* (2005)
Phosphorus is found in the soil in several forms that vary according to the chemical nature of the compounds and the bound energy. Therefore, methods for routine evaluation for the availability of P to plants should be able to extract the forms that sustain the plant uptake. This study evaluated the mode of action of Mehlich-1, Mehlich-3 and anion exchange resin (AER) methods by observing the modifications in soil P forms after three and thirteen successive extractions. Samples of a Rhodic Hapludox that had been cultivated under no-tillage and treated with annual doses of 0, 30, 60, 90, and 120 kg ha -1 P2O5, totalling 0, 180, 360, 540, and 720 kg ha-1 P2O5 throughout the previous six years were used. After the successive extractions, the remaining soil was oven-dried and submitted to soil P fractionation according to Hedley's procedure. Results showed that Mehlich-1 and AER methods extract mainly the inorganic forms, and a portion of desorbed P is readsorbed to the colloids. Mehlich-3 promotes the desorption of inorganic and organic P forms. Phosphorus desorption by Mehlich-1, Mehlich-3 and AER occurs according to its lability in the soil, extracting the most labile forms first, followed by those of lower lability.